Las competencias del docente de maestría en universidades colombianas : apreciaciones de alumnos y profesores. (2016)
This article shows the results of research on the teaching competency view from the perspective of its protagonists: teachers and apprentices. The study design is descriptive ex post facto from the empirical-analytical methodology, composed of quantitative methods, from instruments such as questionnaires and sources linked to master’s programs (teachers and students). Its objective is to analyze the informants’ appreciation of the current teaching profile and their required competency needs, all from the teaching and research task. The results prove significant differences that show a set of needs for teacher training. Finally, some reflections are presented for an improvement of the formation of trainers in the analyzed context.